The Empirics of Exchange Rate Regimes and Trade Words vs. Deeds - Qureshi, Mahvash Saeed (International Monetary Fund, 2010)
This paper examines the impact of exchange rate regimes on bilateral trade while differentiating the effects of ""words"" and ""deeds"". Our findings-based on an extended database for de jure and de facto exchange rate classifications-show that while fixed exchange rate regimes increase trade, there is no systematic difference in the effects of policy announcements versus actions to maintain exchange rate stability. The trade generating effect of more stable exchange rate regimes is however more pronounced when words and actions are aligned, both in the short and long-run. Policy credibility therefore plays an important role in determining the effects of de jure and de facto exchange rate arrangements such that deviations between the two could be costly. In addition, we find evidence that (i) the impact of hard pegs such as currency unions is broadly similar to that of conventional pegs; (ii) the currency union and direct peg effects evolve over time; and (iii) the effects of more stable regimes are heterogeneous across country groups